Prevalence of self-mutilation seen in the cases of suicide at the Johannesburg Forensic Pathology Service - Gobey, Erin (My University, 2014)
The act of self-mutilation has sparked much interest over the years. Various research has been conducted into this phenomena with researchers asking questions about why some individuals self-mutilate, what psychological functions self-mutilation may serve, who is most affected by self-mutilation and what are the links between self-mutilation and other forms of psychopathology. This research study considered the prevalence of self-mutilation seen in the cases of suicide at the Johannesburg Forensic Pathology Service Medico-Legal Mortuary. This study was a prospective and descriptive study which considered the available literature on the phenomenon of self-mutilation and its link with suicide. This study also observed the external patterns of injury associated with the method of suicide as well as self-mutilation. It was found that self-mutilation is prevalent in 8 % of the suicide population in Johannesburg and that it was more common in men. The most common chosen method of suicide seen in this sample was that of toxicity of ingested substance. The second most common method of suicide in the self-mutilation was that of hanging. Future recommendations and future areas of research were also identified suggesting that there is still much information which needs to be gathered on the phenomenon of self-mutilation, especially within the South African context.
Submitted in fulfillment of the requirements for the degree of Masters of Science in Medicine In the Health Science Faculty University of Witwatersrand Johannesburg February 2014
Keywords: Self Mutilation